Urgency and Strategy for Developing HOTS Questions in Arabic Language Learning in the 21st Century Skills Era - Muhammad Nashrul Amrullah; Moh Abdul Kholiq Hasan (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the urgency and strategies for developing Higher Order Thinking Skills (HOTS) questions in Arabic language learning in the era of 21st-century skills. This research employs a qualitative approach using a library research method, with data sources derived from books, scholarly journal articles, and relevant academic documents. Data collection was conducted through documentation techniques, while data analysis used a descriptive-analytical method.The results indicate that the development of HOTS-based questions in Arabic language learning is highly urgent in addressing the demands of 21st-century skills, which include critical thinking, creativity, communication, and collaboration. From the perspective of the revised Bloom’s taxonomy, HOTS is positioned at higher cognitive levels, namely analyzing (C4), evaluating (C5), and creating (C6), which encourage students to think more deeply and critically.The strategies for developing HOTS questions include analyzing basic competencies, constructing test blueprints, utilizing contextual stimuli, designing items based on higher-order cognitive levels, and developing scoring guidelines. The implementation of these strategies not only improves the quality of assessment but also contributes to the development of students’ 21st-century skills comprehensively. Therefore, the development of HOTS questions in Arabic language learning plays a strategic role in enhancing the quality of education and preparing students to face global challenges in the future.